Did diogenites form from diogenites?: A case of Yamato diogenites - Masuda, Akimasa; Nakamura, Noboru; Shimizu, Hiroshi; Tanaka, Tsuyoshi (1981)
P(論文) It has been found that the REE distribution in Y-74010 is considerably different between two adjacent fragments, sizes of which are at least 500mg, a fact indicative of patchy heterogeneity. In addition, it is worthwhile to note that the abundance ratios between two fragments in question are a linear function of atomic number. On the other hand, Y-74013 can be interpreted as a mixture of two distinct constituents, i.e., relatively coarse-grained pyroxene and much finer pyroxenic remnant component. It is noted that these two constituents of Y-74013 can correspond to two different kinds of parts represented by macroscopically separated patches of Y-74010 mentioned above. These observations coupled with the basically linear abundance ratios relative to atomic number suggest that (1) intense melting took place for a parental body of the Yamato diogenites, (2) two separate components reflect the coexisting solid and liquid phases and (3) the solid phase was formed from liquid, transiently as a low-Ca clinopyroxene, which subsequently changed into orthopyroxene as a finally stable form. Also it is an interesting fact that the apparent REE partition function pertaining to Y-692 appears to show discrete (quantum-like) effect. departmental bulletin paper